Vocabulary Discovery Strategy: A Case Study on Autism Spectrum Disorder Students - Adnyani, Luh Diah Surya; Laksono, Kisyani; Anam, Syafi'ul; Padmadewi, Ni Nyoman (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Language learners utilize vocabulary learning strategies (VLS) to learn new words. Although VLS was widely used, there was a lack of research about how it was utilized by students with autism spectrum disorder (ASD). This case study sought to analyze the VLS, especially the discovering strategy, employed by four primary school students with ASD. Schmitt's taxonomy framework was used in this study. A case study methodology was employed in this study. An observation lasting nine months, four weeks in a month, and four hours in a day was conducted due to the inability of those students to fill out the questionnaire, which was often a requirement in previous studies. Furthermore, the interviews with teachers enhanced and elucidated the findings. The data were encoded utilizing a blend of bottom-up (inductive) and top-down (deductive) methodologies and analyzed through thematic analysis. The results indicate that students with ASD utilize the strategy groups according to Schmitt's taxonomy. They learn and understand new English vocabulary through determination and social strategies. This study emphasizes that students with ASD also utilize additional strategies not specified in Schmitt's taxonomy and cannot learn new English vocabulary independently. The teacher's intervention is necessary. This paper presents the practical implications of the findings for teachers who work with students with ASD. Additionally, the necessity for further research in this area is discussed.